Exploring the role of values-based leadership in promoting ethical conduct in schools: a case study of two schools in Gauteng - Rafout, Khensani Esther (My University, 2020)
For many years literature reiterated the great impact values-based leadership has to curb ethical conduct, positive organisational culture and ill-behaved learners in schools. This study focuses on the role that value-based leadership plays in the ethical conduct of primary school management. Hence, the study seeks to understand and explain the relationship between value-based leadership and ethical conduct of educators and leadership as well as learner behaviour in schools. The central claim is to adopt the value-based leadership approach so that schools experience less cases of unethical conduct among teaching and management staff which in turn hope to reduce learner’s ill behaviour. A qualitative research approach and case study design was utilised to investigate the phenomenon. Data was generated through interviews and document reviews. Thematic analysis was applied to provide a rich and dense description of the results. The results indicated that schools with values were more effective in teaching and learning and had fewer cases of unethical behaviour and ill-disciplined learners. These findings corroborated with the assumptions of the study which states that without common beliefs and values an organisation ceases to exist. In summary I articulate that principals need to establish and maintain shared values and be more diverse in their perceptions of values because the value-based leadership (VBL) approach because it provides ways of overcoming deficiencies in leadership and aims to recognise everyone's values in the school.
A research report submitted in partial fulfilment of the requirements for the degree of Master of Education to the School of Education in the Faculty of Humanities at the University of Witwatersrand, Johannesburg, 2020
Keywords: Education-South Africa; Leadership